The Materials and Craft of Early Iconographers - Leonida, Mihaela D. (SpringerBriefs in Materials,, 2014)
This book describes in detail the materials and techniques used by medieval iconographers. It offers information about the natural sources, the raw materials, the tools and the technologies involved in preparing them. The book allows entry into the secretive world of very knowledgeable and skilled artisans, about which very little is known. Topics covered include raw materials, pigments, binders, solvents, adhesives, inks and varnishes. Special chapters will be dedicated to the fresco technique as practiced by the early iconographers, grinding, painting on glass and the training/apprenticeship of these craftsmen.